2009
DOI: 10.1371/journal.pone.0006958
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal Microbiota Regulate Xenobiotic Metabolism in the Liver

Abstract: BackgroundThe liver is the central organ for xenobiotic metabolism (XM) and is regulated by nuclear receptors such as CAR and PXR, which control the metabolism of drugs. Here we report that gut microbiota influences liver gene expression and alters xenobiotic metabolism in animals exposed to barbiturates.Principal findingsBy comparing hepatic gene expression on microarrays from germfree (GF) and conventionally-raised mice (SPF), we identified a cluster of 112 differentially expressed target genes predominantly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
166
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 212 publications
(181 citation statements)
references
References 39 publications
7
166
0
2
Order By: Relevance
“…Evidence is now emerging that the presence of a gut microbiota can alter key host enzymes involved in xenobiotic metabolism. For example, multiple studies have shown that the hepatic expression of CYP450 genes differs between the conventional and the germ-free state (60)(61)(62). Germ-free mice showed increased expression of P450 oxidoreductase, the sole electron donor for type II CYP450 enzymes, and increased expression of the constitutive androstane receptor (CAR), which serves as the master regulator of hepatic xenobiotic metabolism (62).…”
Section: R E V I E W S E R I E S : G U T M I C R O B I O M Ementioning
confidence: 99%
“…Evidence is now emerging that the presence of a gut microbiota can alter key host enzymes involved in xenobiotic metabolism. For example, multiple studies have shown that the hepatic expression of CYP450 genes differs between the conventional and the germ-free state (60)(61)(62). Germ-free mice showed increased expression of P450 oxidoreductase, the sole electron donor for type II CYP450 enzymes, and increased expression of the constitutive androstane receptor (CAR), which serves as the master regulator of hepatic xenobiotic metabolism (62).…”
Section: R E V I E W S E R I E S : G U T M I C R O B I O M Ementioning
confidence: 99%
“…51 Recent studies also point to the involvement of the microbiota in the development of personalized medicine 52 and in xenobiotic metabolism. 53 Certain environmental toxins and drugs are metabolized by the gut microbiota into less or more harmful substances. Several biological active compounds are also produced by the gut microbiota such as short chain fatty acids (SCFAs), conjugated linoleic acid, phenoles, indoles, or trimethylamine.…”
Section: Gut Microbiotamentioning
confidence: 99%
“…In both host-associated and in natural ecosystems, microbial processes are responsible for the maintenance of ecosystem health. The mammalian GI microbiome has been shown to make additional contributions to host health by producing vitamins [20], metabolizing, and modulating host responses to xenobiotics [21,22], attenuating inflammatory responses [23], increasing resistance to pathogenic bacteria, assisting in the development of the immune system [24], development and function of the brain [25], and modulating behavior [25][26][27]. Although less well described, microbiomes found in other animal-associated niches are equally intriguing in their health-promoting properties.…”
Section: Introductionmentioning
confidence: 99%